Governance of public science and technology organizations from managerial theory perspectives and implications for Vietnam - Dang Thu Giang (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
Public science and technology organizations are the pillars of the national innovation system, playing a central role in creating knowledge, developing technology and transferring it to production and life practices. However, the practice of governance of these organizations in Vietnam is currently facing many challenges in terms of institutions, financial mechanisms, human resources, autonomy and efficiency of linking with businesses. In order to solve the root of these problems, it is very necessary to study and apply the foundations of modern management theories, especially the agency theory, the theory of property rights and new public management. This approach not only helps to identify the nature of bottlenecks in the governance of public science and technology organizations, but also serves as a scientific basis for proposing innovative solutions in accordance with Vietnam's characteristics in the context of integration and development. The article consists of 05 contents: (1) Background; (2) The connotation of public organization governance; (3) Theoretical basis for governance of public science and technology organizations; (4) Vietnam’s practice from a theoretical perspective; (5) Lessons drawn from theoretical perspectives. Code: 25060502